Kiai Haji Arsyad: Pejuang Kemerdekaan Era Revolusi Fisik di Lampung - Fitriani, Lutfia; Karsiwan, Karsiwan (Yayasan Alpatih Harapan Semesta, 2023)
The aim of this research is to find out the biography of K.H Arsyad from the time he fought until he died. And knowing the traces of K.H Arsyad's independence struggle in the revolutionary era in Lampung. The method used in this research is a historical research method, because this research takes objects from events that occurred in the past. The steps in historical research are: (1) Heuristics is a search process to find historical sources. (2) Criticism is investigating whether historical traces are genuine or fake. During the era of the war for independence, the name K.H. Arsyad took many roles with the spirit of jihat fi sabililah to defend the homeland. To liberate the land of blood from the invaders. The events that occurred during the Physical Revolution from 1945 to 1949 were experienced by K.H. Arsyad, namely during the first Dutch military aggression around August 1947. and during the second military aggression around 1949. KH Arsyad's struggle was by physical means which is usually called armed struggle because Lasykar Hizbullah Telukbetung fought against the Dutch colonialists with minimal weapons.